ABDULLA QAHHOR HIKOYALARIDA OʻZARO BOGʻLIQLIK (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article discusses the stories of Abdulla Qahhor, their distinguishing features from others. It also discusses the interconnectedness of the stories.